The Role of Cryotherapy in Vitreous Concentrations of Topotecan Delivered by Episcleral Hydrogel Implant - Martina Kodetova; Radka Hobzova; Jakub Sirc; Jiri Uhlik; Katerina Dunovska; Karel Svojgr; Ana-Irina Cocarta; Andrea Felsoova; Ondrej Slanar; Martin Sima; Igor Kozak; Pavel Pochop (MDPI AG, 2022)
Transscleral diffusion delivery of chemotherapy is a promising way to reach the vitreal seeds of retinoblastoma, the most common intraocular malignancy in childhood. In this in vivo study, the delivery of topotecan via lens-shaped, bi-layered hydrogel implants was combined with transconjunctival cryotherapy to assess whether cryotherapy leads to higher concentrations of topotecan in the vitreous. The study included 18 New Zealand albino rabbits; nine rabbits received a topotecan-loaded implant episclerally and another nine rabbits received transconjunctival cryotherapy superotemporally 2 weeks before implant administration. Median vitreous total topotecan exposures (area under the curve, AUC) were 455 ng·h/mL for the cryotherapy group and 281 ng·h/mL for the non-cryotherapy group, and were significantly higher in the cryotherapy group, similar to maximum levels. Median plasma AUC were 50 ng·h/mL and 34 ng·h/mL for the cryotherapy and non-cryotherapy groups, respectively, with no statistically significant differences between them. In both groups, AUC values in the vitreous were significantly higher than in plasma, with plasma exposure at only approximately 11-12% of the level of vitreous exposure. The results confirmed the important role of the choroidal vessels in the pharmacokinetics of topotecan during transscleral administration and showed a positive effect of cryotherapy on intravitreal penetration, resulting in a significantly higher total exposure in the vitreous.